Cell-mediated immunity (CMI) to human wart virus and wart-associated tissue antigens. - Lee, A K (1976)
Lymphocyte transformation (LT) and leucocyte migration inhibition in agarose were used to demonstrate cell-mediated immune response to purified human wart virus and wart tissue extract in various subjects with warts and those without past history of warts. Most individuals bearing warts for less than 1 year duration showed positive cell-mediated responses to both the virus and tissue extract whereas very few of those who had warts for longer duration responded to either antigenic preparation. The difference was statistically significant. Subjects who had warts in the past also showed positive responses but these tended to decrease in degree with time. Surprisingly a group of subjects who never had warts before also responded to stimulation with the virus, but not to the extract. The positive response to stimulation with wart tissue extract reflects the presence of wart associated antigens other than the virus. Cell-mediated immunity against the wart virus and wart-associated antigens is probably important in preventing the persistence or even establishment of disease but this protective immunity is short-lived. The lack of quantitative correlation between LT and leucocyte migration inhibition demonstrable in this study suggests that these two are separate events in in vitro lymphocyte stimulation with antigens.